2022
DOI: 10.1007/s00405-022-07410-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngolaryngeal semiology and prognostic factors in multiple system atrophy

Abstract: Introduction Multiple system atrophy (MSA) is a rare degenerative neurological disorder in adults. It induces parkinsonian and/or cerebellar syndrome associated with dysautonomia. Pharyngolaryngeal symptoms are common. Our aim is to describe the Pharyngolaryngeal semiology on one hand, and to ascertain whether the presence of these symptoms represents a prognostic factor for MSA on the other. Methods Thus, we carried out a retrospective, single-centre stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Dysphagia, another common presentation of axial symptoms, was also associated with prognosis in previous studies. A previous study reported pharyngeal anomalies was associated with poorer prognosis [ 27 ]. Our study also found worse cognitive impairment in Cluster 3 which had shorter survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia, another common presentation of axial symptoms, was also associated with prognosis in previous studies. A previous study reported pharyngeal anomalies was associated with poorer prognosis [ 27 ]. Our study also found worse cognitive impairment in Cluster 3 which had shorter survival time.…”
Section: Discussionmentioning
confidence: 99%